'Scratching the surface of the taken as given, as a process of unsettling': an interview with Tariq Jazeel about his book Postcolonialism (2019). (2nd October 2022) - Clayton, Daniel; Jazeel, Tariq
ABSTRACT: This interview with Tariq Jazeel, concerning his 2019 book Postcolonialism, was orchestrated by Dan Clayton in 2021 in his capacity (then) as co-editor of the SGJ. The interview is a frequently used medium in postcolonial studies, but one that is much underused in geography, which is maybe strange given critical human geography's core commitment to appraising context and dialogue, and its attentiveness to agency, voice and exclusion, and promotion of new forms of cultural production and knowledge exchange. Dan drafted a set of questions for Tariq to respond to in writing, and this written dialogue was then used as a springboard for an hour-long recorded conversation over Microsoft Teams. These two forms and stages of interview generate a suite of reflections, ideas, and provocations about the postcolonial (and the decolonial and anti-colonial too). The work of unsettling the lingering effects of colonialism in the present – scratching the surface of the taken as given – and how it fosters critique, points to new forms of cultural production, and how the work of unsettling is braided around our own personal and political lives, emerged as a central postcolonial thread through the course of this conversation.